2014
DOI: 10.1002/2014gl061613
|View full text |Cite
|
Sign up to set email alerts
|

Mass changes of outlet glaciers along the Nordensjköld Coast, northern Antarctic Peninsula, based on TanDEM‐X satellite measurements

Abstract: We analyzed volume change and mass balance of outlet glaciers of the northern Antarctic Peninsula over the period 2011 to 2013, using topographic data of high vertical accuracy and great spatial detail, acquired by bistatic radar interferometry of the TanDEM-X/TerraSAR-X satellite formation. The study area includes glaciers draining into the Larsen-A, Larsen Inlet, and Prince-Gustav-Channel embayments. After collapse of buttressing ice shelves in 1995 the glaciers became tidewater calving glaciers and accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 26 publications
7
67
1
Order By: Relevance
“…Crane and Jorum glaciers, terminating in deep and narrow fjords, have been subject to acceleration and major mass depletion during the first 5 years after ice shelf collapse, but slowed down afterwards. Similar behavior after retreat into narrow fjords is observed for Sjögren and Boydell glaciers in the Prince Gustav Channel and for the Dinsmoor, Bombardier and Edgeworth glaciers in the Larsen A embayment (Rott et al, 2014). The ratio of longitudinal stress to lateral shear stress is critical for glacier motion in narrow valleys (Hulbe et al, 2008).…”
Section: Discussionsupporting
confidence: 59%
“…Crane and Jorum glaciers, terminating in deep and narrow fjords, have been subject to acceleration and major mass depletion during the first 5 years after ice shelf collapse, but slowed down afterwards. Similar behavior after retreat into narrow fjords is observed for Sjögren and Boydell glaciers in the Prince Gustav Channel and for the Dinsmoor, Bombardier and Edgeworth glaciers in the Larsen A embayment (Rott et al, 2014). The ratio of longitudinal stress to lateral shear stress is critical for glacier motion in narrow valleys (Hulbe et al, 2008).…”
Section: Discussionsupporting
confidence: 59%
“…Dramatic speedup with subsequent deceleration of former ice shelf tributaries was reported by various authors: e.g., in this sector by Seehaus et al (2015Seehaus et al ( , 2016 at DBE and Sjögren Inlet glaciers and further south at Larsen B embayment by Rott et al (2011) and Wuite et al (2015). The velocities reported by Rott et al (2014) at Sjögren, Pyke, Edgeworth and Drygalski glaciers are generally higher than our findings. The authors measured the velocities at locations near the center of the glacier fronts, where the ice flow velocities are typically highest, whereas we measured the median velocities at cross profiles close to the glacier fronts (Seehaus et al, 2015).…”
Section: East-ice-shelfsupporting
confidence: 66%
“…S16 in the Supplement) are nearly stable with short-term variations in the order of 0.2-0.5 m d −1 between 1993 and 2014. Rott et al (2014) also found nearly constant flow velocities at Pyke Glacier (part of the APPE basin, Table 1). The authors suggest that the ice flow of APPE glaciers was not strongly disturbed by the ice shelf removal due to the steep glacier surfaces and shallow seabed topography at the glacier fronts (Pudsey et al, 2001).…”
Section: East-ice-shelfmentioning
confidence: 66%
See 1 more Smart Citation
“…This is inherent to the use of a radar altimeter over rough terrain: the system unavoidably oversamples high areas within the beam footprint. However, detailed study of a set of glacier outlets that formerly fed the Larsen A and Prince Gustav ice shelves (which were the site of major ice shelf disintegrations in 1988 and 1995) suggests some parts of our study area have begun to see a slightly reduced level of ice mass loss in the 2011-2013 period (Rott et al, 2014).…”
Section: Discussionmentioning
confidence: 88%